Lysosomes as Oxidative Targets for Cancer Therapy. (5th July 2017) - Dielschneider, Rebecca F.; Henson, Elizabeth S.; Gibson, Spencer B.
Abstract : Lysosomes are membrane-bound vesicles that contain hydrolases for the degradation and recycling of essential nutrients to maintain homeostasis within cells. Cancer cells have increased lysosomal function to proliferate, metabolize, and adapt to stressful environments. This has made cancer cells susceptible to lysosomal membrane permeabilization (LMP). There are many factors that mediate LMP such as Bcl-2 family member, p53; sphingosine; and oxidative stress which are often altered in cancer. Upon lysosomal disruption, reactive oxygen species (ROS) levels increase leading to lipid peroxidation, mitochondrial dysfunction, autophagy, and reactive iron. Cathepsins are also released causing degradation of macromolecules and cellular structures. This ultimately kills the cancer cell through different types of cell death (apoptosis, autosis, or ferroptosis). In this review, we will explore the contributions lysosomes play in inducing cell death, how this is regulated by ROS in cancer, and how lysosomotropic agents might be utilized to treat cancers.